Azo-functionalised metal–organic framework for charge storage in sodium-ion batteries. Issue 10 (13th January 2023) - Desai, Aamod V.; Seymour, Valerie R.; Ettlinger, Romy; Pramanik, Atin; Manche, Alexis G.; Rainer, Daniel N.; Wheatley, Paul S.; Griffin, John M.; Morris, Russell E.; Armstrong, A. Robert
Abstract : An azo-functionalised MOF is studied as an electrode material for sodium-ion battery with detailed characterisation of the electrochemical process. Abstract : Sodium-ion batteries (NIBs) are emerging as promising devices for energy storage applications. Porous solids, such as metal–organic frameworks (MOFs), are well suited as electrode materials for technologies involving bulkier charge carriers. However, only limited progress has been made using pristine MOFs, primarily due to lack of redox-active organic groups in the materials. In this work a azo-functional MOF, namely UiO-abdc, is presented as an electrode compound for sodium-ion insertion. The MOF delivers a stable capacity (∼100 mA h g −1 ) over 150 cycles, and post-cycling characterisation validates the stability of the MOF and participation of the azo-group in charge storage. This study can accelerate the realisation of pristine solids, such as MOFs and other porous organic compounds, as battery materials.